Suppressing the liquid product crossover in electrochemical CO2 reduction. (12th January 2021) - Wang, Ning; Miao, Rui Kai; Lee, Geonhui; Vomiero, Alberto; Sinton, David; Ip, Alexander H.; Liang, Hongyan; Sargent, Edward H.
Abstract: Coupling electrochemical CO2 reduction (CO2 R) with a renewable energy source to create high‐value fuels and chemicals is a promising strategy in moving toward a sustainable global energy economy. CO2 R liquid products, such as formate, acetate, ethanol, and propanol, offer high volumetric energy density and are more easily stored and transported than their gaseous counterparts. However, a significant amount (~30%) of  liquid products from electrochemical CO2 R in a flow cell reactor cross the ion exchange membrane, leading to the substantial loss of system‐level Faradaic efficiency. This severe crossover of the liquid product has—until now—received limited attention. Here, we review promising methods to suppress liquid product crossover, including the use of bipolar membranes, solid‐state electrolytes, and cation‐exchange membranes‐based acidic CO2 R systems. We then outline the remaining challenges and future prospects for the production of concentrated liquid products from CO2 . Abstract : Here we review promising methods to suppress liquid product crossover in flow cell reactor including the use of bipolar membranes, solid‐state electrolytes, and cation‐exchange membranes based acidic CO2 R systems. The elimination of liquid product crossover is thus a key step to advance the achievement of renewable liquid fuels from CO2